Adequate Livelihood Security: A Study of the Relevance of State Objectives to the Protection of the Poor and Abandoned Children - Mochammad, Aiman; Adiningsih, Pradipta Noor; Wada, Igam Arya (Jurnal Justiciabelen, 2024)
Indonesia as a state of law in reality often encounters discrepancies between laws and regulations and facts in everyday life, especially related to the guarantee of a decent livelihood. The constitution stipulates that every citizen has been given the right to get a decent job and life solely for respect for human rights. If we look further at the poor, and abandoned children are basically the responsibility of the state to get attention and protection. But the reality is that vagrants and beggars get criminal penalties stipulated in Article 504 and Article 505 of the Criminal Code. This research uses the Normative Juridical research method, which uses a statutory approach and a conceptual approach. This study aims to provide a view related to the fulfillment of the rights of the poor, especially beggars and vagrants. There are several things behind the punishment of beggars and vagrants, one of which is considered to interfere with public interest. This is certainly not in accordance with the conception of the purpose of protecting all and all bloodshed as stated in Article 34 paragraph 1 of the Constitution of the Republic of Indonesia Year 1945, "The poor and abandoned children are cared for by the state". There are regulations issued by the government related to assistance and social security programs, but are not in line with established regulations, such as uneven and inaccurate aid programs distributed to the community.